Development of Online Learning Based Teacher Competency Models - Restuti, Hermasari Sari; Suryanto, Suryanto (STRADA : Jurnal Ilmiah Kesehatan, 2021)
In Indonesia, until May 5 2020, 864 people died from the COVID-19 virus and 11.192 people were confirmed to have contracted COVID-19. The implementation of physical distancing policy requires that the learning process be carried out from home through an online system. The online learning system presents its own challenges for teachers who in this case are teachers. This research aims to improve the development of teacher competence in terms of pedagogic competence, which is the ability of teachers in learning management which includes the ability to utilize the advancement of science and technology in education. In this study,researchers took 5 people as research subjects to be interviewed. The results showed that the development of pedagogic competency model needs to be done to teachers in order to improve and maximize the use of science and technology in online learning,especially during the pandemic period as it is today.